PENGARUH KOMPETENSI DIGITAL DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN PEGAWAI BAGIAN PENGADAAN BARANG/JASA SEKRETARIAT DAERAH KABUPATEN PASURUAN - Dari, Rensi Wulan; Sundjoto; Rahayu, Sri (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of digital competence and work culture on employee performance, both directly and through organizational commitment as a mediating variable. The research subjects were all employees of the Goods/Services Procurement Division at the Regional Secretariat of Pasuruan Regency, totaling 91 individuals. A census method was used, involving the entire population as the sample. Data analysis was conducted using the Partial Least Square (PLS) approach to examine the relationships among variables. The results showed that digital competence had a positive and significant influence on employee performance. Likewise, a supportive and constructive work culture also contributed to performance improvement. Furthermore, organizational commitment was found to be a mediating variable that strengthens the influence of digital competence and work culture on employee performance. Thus, enhancing digital competence and fostering a positive work culture can reinforce organizational commitment, ultimately leading to improved employee performance.